A study on poor sleep hygiene and obesity among different groups of workers in the petroleum industry located in Andhra Pradesh - Dinesh Reddy, Sagam (International Journal Of Community Medicine And Public Health, 2024)
Background: This study explored the relationship between poor sleep hygiene and obesity among workers in the petroleum industry in Andhra Pradesh. Sleep hygiene refers to practices conducive to regular, healthy sleep. Poor sleep hygiene has been linked to health issues, including obesity. Understanding this relationship is crucial for targeted interventions to improve worker health. Methods: A cross-sectional comparative study was conducted with 193 tank drivers and 90 office workers (female workers excluded due to small sample size). Demographic data, including age, BMI, and average sleep duration, were collected via self-report questionnaires. Statistical tests, including independent t-tests and Mann-Whitney U statistics, were used to assess significance. Results: A significant association between poor sleep hygiene and obesity was found among petroleum workers. Those reporting shorter sleep duration, irregular sleep schedules, and frequent sleep disturbances were more likely to be obese compared to those with better sleep practices. Shift work and long hours were identified as contributing to poor sleep and increased obesity risk. Conclusions: Promoting healthy sleep habits is essential to reduce obesity among petroleum workers. Interventions such as sleep hygiene education and workplace policies supporting adequate rest may help mitigate obesity risk. Addressing occupational factors like shift work and long hours is vital for improving overall worker well-being.